Purchasing principles and management - Baily, Peter; Farmer, David H. (London : Pitman, 1981)
It provides a practical guide to all aspects of the purchasing function.
Includes bibliographical references and index.
occ 16/01/2019
Loans
Keywords: Purchasing; Industrial Procurement